Seed Setting under Controlled Natural Cross Pollination in Three Populations of Coconut (Cocas Nucifera L.) - Enaberue, Louis (2015)
The purpose of this study was for high rate production of coconut natural hybrids resulting from controlled natural pollination. The primary objective of this study was to evaluate the seed setting percentage resulting from controlled natural pollination in various cross combinations of coconut (Cocos nucifera L.). A secondary objective was to estimate the effect of climatic factors on number of bunches, number of buttons and number of nuts produced by the cross combinations.